Oryza rufipogon, a valuable source for resistance to bacterial blight of rice - Ram, Tilathoo; Laha, Gouri S.; Deen, Ram; Ramos, Joy M.; Vera Cruz, Casiana M.; Brar, Darshan S. (Wiley, 2011)
With 2 tablesSix hundred and sixty‐two accessions of Oryza rufipogon were screened against two Philippine strains (PXO61 and PXO99) of Xanthomonas oryzae pv. oryzae (Xoo) for their resistance to bacterial blight (BB). Of the 662 accessions, 13.6% were resistant and 7.9% were moderately resistant to PXO61 strain, while 5.7% and 6.8% accessions were found resistant and moderately resistant, respectively, against strain PXO99. The accessions found resistant to one or both the strains were further evaluated with five Philippine isolates and four Indian isolates having different virulence profile. Fourteen accessions were highly resistant to all the five strains of the Philippines, while six accessions were found to have broad‐spectrum resistance to all the four Indian strains of Xoo. Of the 662 accessions screened, only two accessions designated as Acc # 104423 and 80671 were found resistant to all the Philippines and Indian strains making them highly valuable donors for durable broad‐ spectrum resistance to BB.